Mycotoxins in oilseeds and vegetable edible oils: an overview of toxicity, occurrence and exposure☆ - Durant Aurore; Pinton Philippe; Puel Olivier; Oswald Isabelle P. (Oilseeds and fats, crops and lipids, 2025)
Oilseeds and vegetable oils, essential components of the human diet, can be contaminated by various mycotoxins, fungal toxic secondary metabolites. This review presents an overview of (i) the chronic toxicity of mycotoxins, (ii) their occurrence in vegetable oils and oilseeds and (iii) consumer exposure through these foodstuffs. A systematic search was performed to identify reviews, published during the last 10 years, concerning the occurrence of mycotoxins in commonly consumed oils and oilseeds. Around fifteen different mycotoxins were detected, the most common being the regulated mycotoxins: aflatoxins, ochratoxin A, zearalenone, fumonisins and trichothecenes. Emerging mycotoxins such as Alternaria toxins, beauvericin and cyclopiazonic acid were also detected. These toxins have various effects and target multiple organs (kidneys, liver, nervous system, digestive system, etc.) and some of them, such as aflatoxin B1, ochratoxin A and fumonisins, are carcinogenic or possibly carcinogenic to humans. Mycotoxins in oils and oilseeds are sometimes present in quantities exceeding European standards for consumer safety. Although they are consumed in smaller quantities than other food groups (e.g., cereals), the contribution of edible oils to the chronic dietary exposure to various mycotoxins should not be neglected. In the case of certain mycotoxins, such as alternariol monomethyl ether, vegetable oils even account for a significant proportion (around 40%) of average chronic European dietary exposure.